Simultaneous Quantification of Quercetin, Myricetin and Kaempferol in Extracts and Latex of Euphorbia helioscopia Using RP-HPLC - Saleem, Uzma; Ahmad, Bashir; Hussain, Khalid; Ahmad, Mobasher; Irfan Bukhari, Nadeem (Asian Journal of Chemistry, 2014)
Herbal products are consistently inconsistent due to a number of factors and their standardization is tedious task, and considering its importance, the present study aims to develop and validate an easy method for the standardization of extracts/products prepared from Euphorbia helioscopia (Family: Euphobiaceae) which is a traditional medicinal plant. Three pharmacologically active compounds such as quercetin, myricetin and kaempferol were used as analytical markers to develop and validate a reversed-phase HPLC method. The standards were eluted through column (Eclipse XDB-C18, 5 μm, 4.6 × 150 mm) using isocratic mobile phase comprising methanol and 0.2 % phosphoric acid (65: 35, v/v). The flow rate was kept at 1 mL/min, temperature of the column was maintained at 30 °C and detection was carried out at 360 nm. The method was found to be linear for all the three standards in the whole range investigated (R2 = 0.982 to 0.998). The limit of detection (LOD) and limit of quantification (LOQ) for quercetin and myricetin were 0.04 and 0.15 μg/mL, respectively, and kaempferol 0.54 and 1.81 μg/mL. The method showed repeatability and reproducibility with RSD < 5 %. The method was successfully applied to different types of extracts of the plant. Therefore, it is concluded from the study that the method is simple, linear, selective, repeatable and reproducible. Moreover, the method can be applied for the standardization of extracts/exudates of the plant.